Students’ Motivation in English Online Learning during Covid-19 Pandemic at SMA Muhammadiyah Gadingrejo - Ayu Fiddiyasari; Reza Pustika (fsip.teknokrat.ac.id, 2021)
To make students still have a learning process while covid-19 outbreak, the Minister of Education and Culture, Nadiem Anwar Makarim, decided that the teaching and learning process should be conducted online rather than face-to-face. The minister of Education and Culture issued Circular Number 4 of 2020 concerning the Implementation of Education in the Emergency Coronavirus (Covid-19). One example of media to teach the online class is Whatsapp Group. This media is implemented in SMA Muhamamdiyah Gadingrejo as an application to teach English online learning. Therefore, in implementing the WhatsApp Group as media to teach online classes, the teacher should be aware of students’ motivation in joining online learning. In this study, the researcher applied descriptive qualitative to investigate the students’ motivation in English online learning during the Covid-19 Pandemic. The instruments used were a questionnaire and an interview. The total participants of this research were 37 tenth-grade students at SMA Muhamamdiyah Gadingrejo. The questionnaire result shows that total means score of extrinsic motivation is higher than instrumental, integrative, and intrinsic motivation. However, the results from the interview show that most students have instrumental motivation. Ultimately, tenth-grade students at SMA Muhammadiyah Gadingrejo have instrumental and extrinsic motivation in joining English online learning in pandemic.